Modeling the voltage loss mechanisms in lithium-sulfur cells: the importance of electrolyte resistance and precipitation kinetics. - Zhang,T; Marinescu,M; O'Neill,L; Wild,M; Offer,G (Physical Chemistry Chemical Physics, 2015)
Understanding of the complex electrochemical, transport, and phase-change phenomena in Li-S cells requires experimental characterization in tandem with mechanistic modeling. However, existing Li-S models currently contradict some key features of experimental findings, particularly the evolution of cell resistance during discharge. We demonstrate that, by introducing a concentration-dependent electrolyte conductivity, the correct trends in voltage drop due to electrolyte resistance and activation overpotentials are retrieved. In addition, we reveal the existence of an often overlooked potential drop mechanism in the low voltage-plateau which originates from the limited rate of Li2S precipitation.